EXPERIMENTAL REMOTE DETERMINATION OF THE STATIC CHARACTERISTIC OF THE ARC IN TIG WELDING (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
In the conditions of TIG welding, the magnitude of the current is set, but not the voltage of the arc. To determine the arc voltage at a set current, arc length, type of electrode, sharpening angle and others, it is necessary to know the static characteristics of the welding arc. This dependence facilitates the use of simulation modelling methods of welding processes. In the proposed study, the static characteristics of the welding arc in TIG process with 4 types of electrodes were determined experimentally. The magnitude of the current was set in the range of 20 to 200A and the arc voltage was measured. All parameters are measured remotely by a real-time welding monitoring system and transferred to a remote computer via the Internet. Graphs were built based on the recordings, and the numerical results were processed and regression relationships were obtained.